Tuning the CHA framework composition by isomorphous substitution for CO2/CH4 separation - Yue, Qiudi; Halamek, Jakub; Rainer, Daniel N; Zhang, Jin; Bulánek, Roman; Morris, Russell E; Cejka, Jiri; Opanasenko, Maksym (Elsevier Science SA, 2022)
Chemically and structurally flexible zeolites that adapt to coordinate extra-framework cations show a rich variety of gas adsorption behavior. Zeolite framework composition can be tuned to optimize pore geometry and host-guest interaction to improve selectivity. Herein, we report the study on the influence of zeolite framework nature on the separation of CO2/CH4, for CHA system containing variable isomorphously substituted heteroelements (none, B, Al, Ga, and Ti). Their performance has been evaluated by single-component isotherms and the overall separation ability was found to be related to both the geometry of 8-ring pore apertures in CHA and interaction between zeolite host and guest molecules, as revealed by Rietveld refinement of PXRD after dehydration and variable-pressure FTIR spectroscopy. Nearly isotropic geometry of the 8-ring pore opening in Al-CHA (3.84 x 3.89 angstrom) was obtained, while Ga-CHA exhibits the largest distortion (3.76 x 3.93 angstrom). Despite the smallest ionic radius of B, both the pore size of 8-ring (3.76 x 3.86 angstrom) as well as the unit cell volume are the smallest amongst the studied materials. Due to the combination of both the textural and the chemical factors, the maximum CO2 capacity and separation selectivity over CH4 follows the order Al-CHA > Ga-CHA > B-CHA approximate to Si-CHA > Ti-CHA. These observations suggest that tuning the framework composition of zeolite can strongly influence the separation of small molecules such as CO2 and CH4.
Vylepšení CHA mřížkové struktury pro CO2/CH4 separaci pomocí izomorfní substituce
Keywords: chabazite; isomorphous substitution; framework composition; adsorbate-adsorbent interaction; CO2/CH4 separation; chabazit; izomorfní substituce; interakce adsorbát-adsorbent; CO2/CH4 separace